2014
DOI: 10.1111/acer.12472
|View full text |Cite
|
Sign up to set email alerts
|

“Wired,” Yet Intoxicated: Modeling Binge Caffeine and Alcohol Co‐Consumption in the Mouse

Abstract: Background The combination of highly caffeinated ‘energy drinks’ with alcohol (ethanol) has become popular among young adults and intoxication via such beverages has been associated with an elevated risk for harmful behaviors. However, there are discrepancies in the human literature regarding the effect of caffeine on alcohol intoxication, perhaps due to confounding factors such as personality type, expectancy, and history of exposure. Animal models of co-exposure are resistant to such issues, however, the con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
28
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(41 citation statements)
references
References 41 publications
(75 reference statements)
11
28
2
Order By: Relevance
“…Indeed, one previous study showed that pre-treatment with DPCPX attenuated the development of rapid tolerance to alcohol’s ataxic effect in mice (Batista et al, 2005), suggesting that A 1 receptor activation is involved in the adaptive response to alcohol intoxication. Our lab and others have shown that longer DID access (~2-4 weeks opposed to 1 week) produces ataxic tolerance (Linsenbardt et al, 2011), alterations in associated locomotion (Linsenbardt and Boehm, 2014, Linsenbardt et al, 2011, Fritz et al, 2014a), and the rate of alcohol intake (Wilcox et al, 2014, Linsenbardt and Boehm, 2014), perhaps indicating that the duration of alcohol access in this model may also alter sensitivity to one or both of these compounds. In addition, animals in our study were freely consuming alcohol in their home cage versus operant chambers in other studies.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Indeed, one previous study showed that pre-treatment with DPCPX attenuated the development of rapid tolerance to alcohol’s ataxic effect in mice (Batista et al, 2005), suggesting that A 1 receptor activation is involved in the adaptive response to alcohol intoxication. Our lab and others have shown that longer DID access (~2-4 weeks opposed to 1 week) produces ataxic tolerance (Linsenbardt et al, 2011), alterations in associated locomotion (Linsenbardt and Boehm, 2014, Linsenbardt et al, 2011, Fritz et al, 2014a), and the rate of alcohol intake (Wilcox et al, 2014, Linsenbardt and Boehm, 2014), perhaps indicating that the duration of alcohol access in this model may also alter sensitivity to one or both of these compounds. In addition, animals in our study were freely consuming alcohol in their home cage versus operant chambers in other studies.…”
Section: Discussionmentioning
confidence: 64%
“…Recently, we demonstrated that the addition of caffeine (a nonselective adenosine receptor antagonist) to a 20% ethanol solution significantly altered the intoxication profile of male C57BL/6J (B6) mice induced by voluntary binge-like consu1mption via the ‘Drinking-in-the-Dark’ (DID) paradigm (Fritz et al, 2014a). The DID paradigm has been validated as a ‘binge’ paradigm as mice will consistently drink alcohol to reach blood alcohol concentrations in excess of 80-100 mg/dl in a short period of 2 hours (aligning with the aforementioned NIAAA definition of binge drinking) and demonstrate significant motor and cognitive impairment as a result of alcohol consumption in this paradigm (Sprow and Thiele, 2012, Fritz et al, 2014a). Specifically, we observed that the addition of caffeine attenuated ataxia and sedation induced by voluntary binge alcohol consumption, although caffeine did not influence alcohol-induced anxiolysis, memory interference, or alcohol intake.…”
Section: Introductionmentioning
confidence: 99%
“…These results indicate that repeated co-exposure to ethanol and caffeine produces a much larger effect than repeated exposure to either drug alone. A recent report by Fritz and colleagues using a voluntary consumption model in the home cage hinted at the possibility that repeated exposure to a combination of ethanol and caffeine could produce a sensitized locomotor response (Fritz et al , 2014), though the effect was not reported as significant. Another report indicated that an ethanol sensitization effect could be enhanced in mice when acutely challenged with a mixture of an energy drink and ethanol, particularly in those mice in which the ethanol sensitization effect is small (Ferreira et al , 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, a 15 mg/kg dose in mice yields nearly similar blood levels of caffeine (~15 μg/ml) as the 500 mg dose in humans (Kaplan et al , 1989), providing some relevance to our choice of dose in this set of experiments. Moreover, ethanol appears to increase caffeine’s half-life in humans (George et al , 1986) though this may not be true in mice (Fritz et al , 2014). Therefore, consideration of higher caffeine doses is important in the context of energy drink consumption, not only because of the higher concentration of caffeine in some of these drinks, but also that many people could already have significant amounts of caffeine in their body from other sources.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation